The Effectiveness of the Instagram Account @visitmadinacom as a News Aggregator for Fulfilling Followers Information Needs - Juni Hidayati Batubara; Andini Nur Bahri (Jurnal Ilmiah Syi'ar, 2025)
This research aims to evaluate how effective the Instagram account @visitmadinacom is as a news aggregator in fulfilling followers' information. The problem in this study lies in the utilization of Instagram, which is generally known as social media for sharing daily activities. However, on the @visitmadinacom account, the function of Instagram not only as a means of sharing activities, but also acts as a news aggregator. This account utilizes Instagram as a medium for disseminating information and news with credible and verifiable sources. This shows a shift in the function of social media from just an entertainment stage to information media that has journalistic value. This research uses a quantitative method with a descriptive approach. Data was collected through a Likert scale-based questionnaire to 100 respondents who are followers of the account. The results showed that the @visitmadinacom Instagram account obtained an average score of 3.39 from 7 indicators measured, namely: credibility, content, context, clarity, continuity and consistency, channel, and audience capability. This score indicates that the @visitmadinacom Instagram account is in the “very effective” category in meeting the information needs of its followers.Based on these findings, it can be concluded that the @visitmadinacom Instagram account successfully fulfills followers' needs for news information about Mandailing Natal. Not only that, the @visitmadinacom Instagram account also effective as a digital tourism promotion media, because it is able to convey messages in an attractive, interactive manner, and in accordance with the characteristics of the audience. This makes the account one of the optimal examples of using Instagram in supporting the promotion of religious tourist destinations.